Routledge handbook on Jerusalem
1 online resource.
Keywords: Few cities around the world transcend their physical boundaries the way Jerusalem does. As the spiritual capital of monotheism, Jerusalem has ancient roots and legacies that have imposed themselves on its inhabitants throughout the centuries. In modern times, and aside from all the religious complexities, Jerusalem has become enmeshed in the Palestinian and Israeli national identities and political aspirations, which have involved and dragged into the fray other actors from around the world. Consisting of 35 chapters from leading specialists, the Routledge Handbook on Jerusalem provides a broad spectrum of studies related to the city and its history. Beginning with a historical overview starting from the end of the Bronze age, the chapters go on to look at a range of topics including: - religious symbolism and pilgrimage - religious and social relations - social and economic history - architecture and archaeology - maps - eschatology - politics By bringing together contributions from leading scholars of different disciplines, this Handbook provides a comprehensive overview of the various layers that make up this unique and special city. It will appeal to students and scholars of Middle East Studies, religion and cultural history, and anyone with an interest in learning more about Jerusalem.